2008
DOI: 10.1177/000312240807300603
|View full text |Cite
|
Sign up to set email alerts
|

Social Control and Youth Suicidality: Situating Durkheim's Ideas in a Multilevel Framework

Abstract: Although the suicide rate among U.S. youth between the ages of 10 to 24 dramatically increased during the past 50 years, little research has examined this outcome within larger social contexts of the adolescent environment. Relying on Durkheim's theory of social integration, we examine the effect of individual- and structural-level social integration on adolescents' suicidality. Using a sample of 6,369 respondents within 314 neighborhoods, we examine the assumptions that high levels of religious, familial, nei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
97
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 87 publications
(191 reference statements)
2
97
0
Order By: Relevance
“…As is weU known, Durkheim attributed group suicide rates to group levels of social integration and moral regulation and famously concluded that "suicide varies inversely with the degree of integration of the social groups of which the individual forms a part" (Durkheim 1897(Durkheim /1952. In Une wifl\ Durkheim, scholars of suicide highlight the importance of social ties for social integration and social regulation (Breault 1986;Johnson 1965;Maimón and Kuhl 2008;PescosoUdo and Georgianna 1989;Stack 2000b;van Tubergen, Grotenhuis, and Ultee 2005;Wray, Colen, and PescosoUdo 2011).…”
Section: Understanding State and Regional Suicide Ratesmentioning
confidence: 99%
“…As is weU known, Durkheim attributed group suicide rates to group levels of social integration and moral regulation and famously concluded that "suicide varies inversely with the degree of integration of the social groups of which the individual forms a part" (Durkheim 1897(Durkheim /1952. In Une wifl\ Durkheim, scholars of suicide highlight the importance of social ties for social integration and social regulation (Breault 1986;Johnson 1965;Maimón and Kuhl 2008;PescosoUdo and Georgianna 1989;Stack 2000b;van Tubergen, Grotenhuis, and Ultee 2005;Wray, Colen, and PescosoUdo 2011).…”
Section: Understanding State and Regional Suicide Ratesmentioning
confidence: 99%
“…Family closeness, produced by positive family exchanges, plays a critical role in facilitating a sense of security, healthy decision-making, better coping skills, and reduction in adolescent problem behavior (Ackard, Neumark-Sztainer, Story, & Perry, 2006). Strong connections to parents provide emotional stability for the adolescent above and beyond other important relational contexts (e.g., school) (Maimon & Kuhl, 2008) and are consonant with the emphasis in Durkheim’s theory that family support and closeness matter to the psychosocial well-being of an adolescent. Indeed, supportive family settings contributed to the development of a positive sense of self for African-American adolescents (Bean, Bush, McKenry, & Wilson, 2003) and fostered better global well- being and socio-emotional adjustment (Demo & Acock, 1996).…”
Section: Familymentioning
confidence: 70%
“…Besides familial structure, the affective domains of family (e.g., closeness, support) have been identified as important elements of integration (Maimon & Kuhl, 2008). Family closeness, produced by positive family exchanges, plays a critical role in facilitating a sense of security, healthy decision-making, better coping skills, and reduction in adolescent problem behavior (Ackard, Neumark-Sztainer, Story, & Perry, 2006).…”
Section: Familymentioning
confidence: 99%
See 1 more Smart Citation
“…A study of 683 eighth and ninth graders, 49% ofwhich self-identified as Protestant, revealed the females have higher levels of depression than males (Milot & Ludden, 2009). Additionally, suicide is the third leading cause of death among 15 to 24 years-old in the United States, with females more likely to attempt suicide than males (Maimon & Kuhl , 2008).…”
Section: Bible Department Gender Issues Student Behaviors and Issuesmentioning
confidence: 99%